Extended haplotype-phasing of long-read de novo genome assemblies using Hi-C - Zev N. Kronenberg (Nature Portfolio, 2021)
Methods to produce haplotype-resolved genome assemblies often rely on access to family trios. The authors present FALCON-Phase, a tool that combines ultra-long range Hi-C chromatin interaction data with a long read de novo assembly to extend haplotype phasing to the contig or scaffold level.